Proceedings of the 4th Information Interaction in Context Symposium 2012
DOI: 10.1145/2362724.2362748
|View full text |Cite
|
Sign up to set email alerts
|

Supporting children's web search in school environments

Abstract: Nowadays, the Internet represents a ubiquitous source of information and communication. Its central role in everyday life is reflected in the curricula of modern schools. Already in early grades, children are encouraged to search for information on-line. However, the way in which they interact with state-of-the-art search interfaces and how they explore and interpret the presented information, differs greatly from adult user behaviour.This work describes a qualitative user study in which the Web search behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, older children will present more sophisticated skills than younger children. The role of cognitive developmental levels is fundamental to understand youth's information behaviour based on age (Eickhoff et al, 2012; Gossen et al, 2014), school grade level (Vanderschantz & Hinze, 2017) and reading literacy skills (Coiro & Dobler, 2007; Lazonder et al, 2020). These studies often compare youth's information behaviour (e.g., quality of search queries and criteria to judge information) with those expected from adults.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, older children will present more sophisticated skills than younger children. The role of cognitive developmental levels is fundamental to understand youth's information behaviour based on age (Eickhoff et al, 2012; Gossen et al, 2014), school grade level (Vanderschantz & Hinze, 2017) and reading literacy skills (Coiro & Dobler, 2007; Lazonder et al, 2020). These studies often compare youth's information behaviour (e.g., quality of search queries and criteria to judge information) with those expected from adults.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a recent interest in investigating search characteristics of young users [9], [19]. Some of these works are based on case studies with a group of young users [20]- [22], while the others utilize search engine logs to analyze search behavior of such users [9], [19], [23], [24]. One of the critical findings is that young users have difficulty in formulating queries for both general search tasks [19] and schoolrelated (educational) tasks.…”
Section: A Educational Searchmentioning
confidence: 99%
“…Second, there is substantial potential for leveraging speech interfaces to address a number of challenges that children face with current text-based search practices. Log analysis has found that children's web searches are frequently "unsuccessful" and "confused" [13,14]. The major challenges identified in previous investigations of children's web search include spelling, typing, and query formulation [10,11].…”
Section: Children's Informational Query Practicesmentioning
confidence: 99%